Integration of Agile Governance ini Maritime Safety System Development (SiKaPal): Adaptive Governance Model in the Archipelago Region of Sumenep Regency - Shoumi Shafira; Wilda Rasaili (Yayasan Ilomata, 2026)
Sumenep Regency comprises 126 islands across 19 mainland and 8 maritime districts, resulting in high dependence on sea transportation and increased maritime safety risks. Between 2020 and 2023, official records show 20–30 maritime accidents annually, including ten major incidents causing nearly 100 fatalities. These conditions expose limitations in conventional governance approaches. In response, the local government implemented an agile governance framework through the Maritime Safety System (SiKaPal). Using a qualitative descriptive method based on in-depth interviews and thematic analysis, this study finds that agile governance improved emergency responsiveness, coordination, resource efficiency, and institutional adaptability in maritime safety management. This study adopts a qualitative descriptive approach to capture in-depth insights into the implementation of agile governance in maritime safety management. Data were collected through semi-structured, in-depth interviews with 20 informants, comprising policymakers, policy implementers, supervisory officials, and community members as policy beneficiaries. The data were analyzed using thematic analysis, focusing on patterns related to governance adaptability, institutional coordination, resource efficiency, and emergency responsiveness. The findings reveal that the integration of agile governance within SiKaPal has produced several significant outcomes. First, budget utilization became more efficient due to flexible planning and iterative evaluation mechanisms. Second, emergency response to maritime accidents was substantially accelerated through improved information flows and inter-agency collaboration. Third, preventive preparedness was strengthened by enhancing early warning systems and community engagement. In addition, agile governance contributed to improving human resource competencies through continuous learning processes and reinforced inter-institutional coordination among relevant stakeholders. This study concludes that agile governance constitutes an effective and contextually relevant governance framework for addressing complex maritime safety challenges in archipelagic regions. The integration of agile principles in the development of SiKaPal has not only improved operational efficiency and responsiveness but also strengthened institutional adaptability and collaborative capacity. Therefore, agile governance offers a strategic model for reinforcing adaptive public service systems in coastal and island-based administrations and holds strong potential for replication in other archipelagic governance contexts.